De novo missense variants in LMBRD2 are associated with developmental and motor delays, brain structure abnormalities and dysmorphic features. Issue 10 (20th August 2020) - Malhotra, Alka; Ziegler, Alban; Shu, Li; Perrier, Renee; Amlie-Wolf, Louise; Wohler, Elizabeth; Lygia de Macena Sobreira, Nara; Colin, Estelle; Vanderver, Adeline; Sherbini, Omar; Stouffs, Katrien; Scalais, Emmanuel; et al.
Abstract : Objective: To determine the potential disease association between variants in LMBRD2 and complex multisystem neurological and developmental delay phenotypes. Methods: Here we describe a series of de novo missense variants in LMBRD2 in 10 unrelated individuals with overlapping features. Exome sequencing or genome sequencing was performed on all individuals, and the cohort was assembled through GeneMatcher. Results: LMBRD2 encodes an evolutionary ancient and widely expressed transmembrane protein with no known disease association, although two paralogues are involved in developmental and metabolic disorders. Exome or genome sequencing revealed rare de novo LMBRD2 missense variants in 10 individuals with developmental delay, intellectual disability, thin corpus callosum, microcephaly and seizures. We identified five unique variants and two recurrent variants, c.1448G>A (p.Arg483His) in three cases and c.367T>C (p.Trp123Arg) in two cases. All variants are absent from population allele frequency databases, and most are predicted to be deleterious by multiple in silico damage-prediction algorithms. Conclusion: These findings indicate that rare de novo variants in LMBRD2 can lead to a previously unrecognised early-onset neurodevelopmental disorder. Further investigation of individuals harbouring LMBRD2 variants may lead to a better understanding of the function of this ubiquitously expressed gene.